Experimental lateral-torsional buckling behaviour of web tapered I-section steel beams. (1st August 2018) - Tankova, Trayana; Martins, João Pedro; Simões da Silva, Luís; Marques, Liliana; Craveiro, Hélder D.; Santiago, Aldina
Highlights: Full-scale experimental tests on lateral-torsional buckling of web tapered beams. Validation of advanced numerical model based on the experimental results. Comparison of the experimental, numerical and analytical estimations of the resistance. Abstract: Tapered steel members are often chosen instead of prismatic due to a better cross-section utilization along the member, which makes them an interesting and more economical alternative. Although EN1993-1-1 offers several methodologies for the stability verification of steel members and frames, it does not provide a clear guidance for the stability design of such members. Recently, the research group has provided simplified stability verification methodologies for tapered columns and beams. The developed methodologies are based on analytical derivations which were validated with advanced numerical simulations. In order to improve the accuracy of the proposed procedures, full-scale experimental tests on tapered columns, beams and beam-column were carried out. The experiments are used to calibrate a numerical model, incorporating all relevant parameters, such as: geometrical imperfections (local and global) and material imperfections (residual stresses). In this paper, firstly a global overview of the experimental programme on web-tapered steel members is given. The key results from each experiment are summarized; they are further used for the calibration of an advanced numerical model.